An investigation of improvements to electrochemical precipitation of struvite from source separated urine - Malanda, Nicole Mulenga (Department of Chemical Engineering, 2017)
Access to decent sanitation remains a problem in developing countries. At the same time, sanitation technology is constantly evolving specifically regarding resource recovery solutions. Some chemical elements found in human excreta derived from non-renewable resources, and the recycling of phosphorous from sewage in particular is a possible solution to the growing issue of resource scarcity. A potential way to recover phosphorous from urine or water-borne sewage is through struvite precipitation. Struvite (MgNH₄PO₄. 6H₂O) is a mineral that can be used as a slowrelease magnesium, ammonium and phosphate based fertilizer and can be produced from urine by adding magnesium to the ammonium and phosphate rich urine. Usually, magnesium is dosed chemically using salts such as MgCl₂, MgO, MgSO₄ or bittern, together with pH regulating agents but these reactants produce unfavourable chemical by-products and the process tends to be expensive. Previous studies have proven that electrochemical dosing of magnesium is a feasible and reliable method of struvite precipitation. It not only produces high grade struvite that is valuable and marketable, but it also eliminates the need for alkalinity dosing in order to create a suitable pH environment for struvite precipitation. Further to that, electrochemical precipitation does not produce any harmful chemical by-products. Previous work shows that one main challenge that is associated with this method is the formation of a mineral layer on the magnesium anode called nesquehonite (MgCO₃ · 3H₂O). This leads to increased electrode potentials and hence high energy consumptions and may also lead to system failures of the reactor. Further to that, struvite generally precipitates as small crystals that are difficult to separate from the solution, leading to low mass recoveries of the product. These small crystals are formed as a result of the high supersaturation, which generally occurs for most processes that are employed to make struvite. In view of these problems, this dissertation presents an investigation of the potential improvements to the electrochemical precipitation of struvite from source-separated urine. The main aim is to minimise or eliminate the formation of mineral precipitates on the anode surface. It also looks into ways of increasing the crystal sizes of the struvite being precipitated in the electrochemical system. The methodology for this investigation involved modelling and experimental work. The specific objectives for this study were to: a) Investigate how thermodynamic modelling of struvite precipitation compares to the experimental results from an electrochemical precipitation reactor, b) Employ the aspect of seeding in an electrochemical reactor for struvite production and determine the technical feasibility of the proposed process, c) Establish how to minimise the formation of nesquehonite so that the quality of struvite produced in the electrochemical reactor is not compromised, d) Investigate how the crystal sizes of the struvite particles produced in the seeded electrochemical precipitation batch reactor setup compare to those produced in the continuously stirred reactor setup with a recycle that gives the particles a longer residence time, e) Investigate the economics and energy requirements of the SEP (Seeded electrochemical precipitation reactor).